(untitled) (Heritage, 2025)
This paper explores the aesthetics of Orthodox values in the poetry of Aleksandar Despotović, viewing them as a continuous thread in the poet’s creative vision and as a fundamental quality of his overall poetics. The concept of the “golden ratio” is contextualized and concluded through an examination of its reception in literary criticism. The analysis demonstrates that Despotović’s creative trajectory, spanning from 1969 to 2005, comprises four interwoven phases or cycles. A survey of these phases reveals that the poet’s faith in God and divine love, as well as his acceptance of the Bible as divine revelation, form the foundation of Orthodox spirituality and the aesthetic core of his poetry and his understanding of love. The essence of both his poetry and travel writing—understood as the poet’s dialogue and communion with God—shows that Despotović discovers in prayer and in the prophetic books of the Bible a renewed beginning and meaning, or, indeed, the aesthetics of his creation and existence. Despotović’s poetic philosophy, viewed through time and space, confirms that the artist consistently develops and deepens his poetic ideas. This philosophy also reveals that love itself has its own prayer, and that prayer occupies a primary place not only in the prayer book but also in the poet’s lexicon. This insight represents a key finding of our critical analysis, particularly in relation to the aesthetic dimension of Orthodox spirituality within Despotović’s oeuvre.